Analisa Koefisien Konveksi Udara Panas Kolektor Surya Plat Datar Yang Dilapisi Cat Absorber Dengan Paintfiller Cangkang Kelapa Sawit - Evi Christiani Sitepu; Diman Raymond S Tambunan (JURNAL VOKASI TEKNIK, 2024)
Solar thermal energy as a very large energy source can be used as an alternative energy source to replace the petroleum energy. One form utilization of solar energy to heat water. In this research solar radiation energy is collected through a device called a solar collector. To get optimal results, the surface of the solar collector is painted with a dull (doff) black color which serves to absorb maximally the intensity of incoming solar radiation and transfer the received heat to the working fluid. This study analyzes the ability of collectors that painted with ordinary paint that also varied paint with oil palm shell paintfiller which is painted on the collector box. Based on the results of the analysis, it was found that in addition to black paint, black paint which was varied with palm oil shells could also be used as a coating on a water heater collector with a convection coefficient of 0,3084 - 0,3133 W/m2.0C and a collector efficiency of 27.64% - 33,00% with water heating heat. 57637.29 - 72049,40 Joules.